Great immortality: studies on European cultural sainthood - Dović, Marijan; Jón Karl Helgason (National cultivation of culture, 2019)
Sacral states : the politics of worship, religious and secular / Joep Leerssen -- Framing the bones of Dante and Petrarch : literary cults and scientific discourses / Harald Hendrix -- Taming a romantic : the canonization of Adam Mickiewicz / Roman Koropeckyj -- The riddles of the Shevchenko cult / Christian Noack -- Hagiographic discourse in the early biographies of France Preseren / Alenka Koron -- Stanko Vraz and the missing saints of the Illyrian movement / Andraz Jez -- Bialik the prophet and the modern Hebrew canon / David Fishelov -- Jacint Verdaguer, a Catalan cultural saint / Magi Sunyer and Jaume Subirana -- "Altars of the Flemish movement" : tombstones and rituals of nation-building / Andreas Stynen -- Hero or traitor? the cultural canonization of Snorri Sturluson in Denmark, Norway, Iceland, and beyond / Simon Halink -- Ilia Chavchavadze : Georgia's cultural saint and a saint of the Georgian Orthodox Church / Bela Tsipuria -- The third canonization of Njegos, the national poet of Montenegro / Bojan Baskar -- Prophet, martyr, saint : Mihai Eminescu's lateral canonization / Andrei Terian -- Antoni Gaudi and Joze Plecnik : two architects on the path from cultural canonization to Catholic beatification / Luka Vidmar -- From the culture of saints to the saints of culture : the saint and the writer between life and work / Jernej Habjan.